Preparation and immunogenicity of vaccine Ac NFU1 (S-) MRC towards the prevention of herpes genitalis. Issue 6 (December 1982) - Skinner, G R; Woodman, C B; Hartley, C E; Buchan, A; Fuller, A; Durham, J; Synnott, M; Clay, J C; Melling, J; Wiblin, C; Wilkins, J
Abstract : A subunit antigenoid vaccine, Ac NFU1 (S-) MRC, was used to prevent primary herpes genitalis in 60 subjects considered to be at risk of this infection. There was no evidence of serious local or general side effects. Neutralising antibody responses were detected in 59% and 90% of subjects receiving the low and high doses of vaccine respectively; immunoprecipitating antibody was detected at a lower frequency, namely in 23% and 43% of subjects receiving the low and high doses respectively. After a mean follow-up period of 18 months none of the vaccinated subjects contracted herpes genitalis after completing the vaccination course.